New Inequality for L-Lipschitzian Functions and Applications - Chhabra, Praphull (Journal of Science and Technology, 2021)
This article gives a really vital and curiously inequality on Jain-Saraswat’s functional discrimination in terms of the Hellinger discrimination and Bhattacharya discrimination by taking into thought L-Lipschitzian functions. Encourage, we outlined a few vital results by utilizing the inferred inequality with numerical confirmation.